1988
DOI: 10.1021/j100327a042
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity behavior of poly(ethylene oxide) in aqueous electrolyte solutions

Abstract: The electrical conductivity of poly(ethy1ene oxide) of different molecular weights in 0.1 M KCl electrolyte solution has been measured in the temperature interval from 0 to 55 "C. The data have been interpreted on the basis of the Looyenga equation for heterogeneous systems, found to apply with good approximation also for other transport properties. The hydration number deduced from these measurements has been estimated to be lower than that reported elsewhere. Its dependence on temperature, however, supports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0
2

Year Published

1994
1994
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 0 publications
5
40
0
2
Order By: Relevance
“…Within the NaCl concentration range (1-17 mM) investigated, the electric conductivity is found to be linear, following Kohlrausch's law Previous studies [3,4,11,12] found that the PEG effect on the electric conductivity depends mainly on the PEG mass concentration, but very weakly on its molecular weight. Wang and Tsao [3] reported a simple exponential function in both dilute and semidilute regimes,…”
Section: Resultsmentioning
confidence: 63%
“…Within the NaCl concentration range (1-17 mM) investigated, the electric conductivity is found to be linear, following Kohlrausch's law Previous studies [3,4,11,12] found that the PEG effect on the electric conductivity depends mainly on the PEG mass concentration, but very weakly on its molecular weight. Wang and Tsao [3] reported a simple exponential function in both dilute and semidilute regimes,…”
Section: Resultsmentioning
confidence: 63%
“…11 shows the measured conductivity along with the predicted reduced conductivity using the Maxwell, Bruggeman, and Meredith and Tobias relations. The Maxwell relation for noninteracting spheres of uniform diameter with conductivity σ d in an external medium with conductivity σ m , is [69] Fig. 11.…”
Section: Effect Of Density On Emulsion Formation and Stability For Comentioning
confidence: 99%
“…[15] Indeed PEG-PEG interaction, mediated by water, is assumed to be driven by cooperative interaction. [14,17] Before comparing the real DDCs with the novel standards, we compare the behavior of the different standards of literature with the novel one. Since FM-and KB-standards are defined in a mass-fixed reference frame it is not quantitatively comparable to our novel standard.…”
Section: Applications Of Distinct Diffusion Coefficients To Poly(ethymentioning
confidence: 99%
“…In fact the exclusion mechanism, responsible for the phase separation of the protein, is different if the PEG molecules are distinct or associated each other. The PEG aggregation and the network formation at high concentration [14,17] make the exclusion efficiency lower. This should be a new key for interpreting the molecular mechanism of the protein-PEG interaction.…”
Section: Applications Of Distinct Diffusion Coefficients To Poly(ethymentioning
confidence: 99%